Plantar pressure and surgical indication of toe arthroplasty for rheumatoid forefoot deformity. Issue 6 (2nd November 2017) - Lee, Hyunho; Ishikawa, Hajime; Miyagawa, Yusuke; Takai, Chinatsu; Nomura, Yumi; Nemoto, Tetsuya; Kobayashi, Daisuke; Abe, Asami; Otani, Hiroshi; Ito, Satoshi; Nakazono, Kiyoshi; Ishii, Takao; et al.
Abstract: Objectives: The objective of this study is to clarify the surgical indication for rheumatoid forefoot deformity according to background characteristics and plantar pressure. Methods: Patients with rheumatoid arthritis were divided into a non-surgical group (group N) and a surgical group (group S). The former consisted of 225 ft, and the latter consisted of 88 ft. DAS28, Japanese Society for Surgery of the Foot rheumatoid arthritis foot and ankle scale (JSSF scale) and hallux valgus angle (HVA) were evaluated as background characteristics. Distribution of peak pressure as plantar pressure was measured in nine sections. Results: In groups N and S, the mean DAS28 was 3.6 and 3.0, the mean JSSF scale was 81.1 and 63.0, and the mean HVA was 19.9° and 35.3°, respectively. The mean peak pressure of group S at the first and third metatarsophalangeal joints was significantly higher compared with group N. Significant differences between the two groups were also seen in Δ pressure (the difference between the maximum and minimum peak pressure values). The cut-off values were 75.0 for JSSF scale, 24.9° for HVA and 3.94 kg/cm 2 for Δ pressure. Conclusions: The combined assessment of HVA and Δ pressure was found to be useful as an indication for surgical treatment of the forefoot.